2013
DOI: 10.5935/1808-8694.20130091
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of the P300 frequency pattern test to assess auditory processing

Abstract: The FPT and P300 are efficient instruments used to assess the intended skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 43 publications
0
17
0
3
Order By: Relevance
“…Therefore, in relation to the maturation of the auditory canal, it is possible to observe better results from birth to, approximately, the age of 12. In relation to behavioral tests, there is a quantitative improvement in the results when age increases (10) . In this study the correlation between normal or altered behavioral test and mean age was not observed.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, in relation to the maturation of the auditory canal, it is possible to observe better results from birth to, approximately, the age of 12. In relation to behavioral tests, there is a quantitative improvement in the results when age increases (10) . In this study the correlation between normal or altered behavioral test and mean age was not observed.…”
Section: Discussionmentioning
confidence: 99%
“…This skill plays an essential role in speech perception, when segmenting speech sounds, in language learning and comprehension, being a prerequisite for reading and writing acquisition (25) , and it is directly related to perception and phonemic discrimination. The auditory attention, assessed through P300, is necessary to the acquisition of acoustic and phonetic aspects of language patterns, which are important when learning how to read and write (10) . In another study in which the relation between the auditory skill of dichotic listening and P300 was made, it was possible to notice that individuals that presented an alteration in the P300 result, also presented some kind of alteration in the dichotic listening test (26) , what corroborates the findings of this study, since the P300 is related to attention and recent memory (10) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations